2013
DOI: 10.1017/s0007114513001475
|View full text |Cite
|
Sign up to set email alerts
|

Long-chain SFA at thesn-1, 3 positions of TAG reduce body fat deposition in C57BL/6 mice

Abstract: The present study aimed to determine the effect of positional distribution of long-chain SFA in TAG, especially at the sn-1, 3 positions, on fat deposition using the C57BL/6 mouse model. Throughout the 15 weeks of the study, mice were fed with diets fortified with palm olein (POo), chemically interesterified POo (IPOo) and soyabean oil (SOY). Mice receiving the SOY-enriched diet gained significantly higher amounts of subcutaneous fat (P¼0·011) and total fat (P¼ 0·013) compared with the POo group, despite simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
19
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 29 publications
6
19
0
1
Order By: Relevance
“…Most of the C16:0 present in lard is located in the internal (Sn-2) position whereas, in palm oil it locates in the external (Sn-1 and Sn-3) positions (Small, 1991;Innis, 2011). This difference might be relevant in further processing for the industry of dry-cured products because FA distribution within the TAG molecule modifies the physical properties of the adipose tissue (Smith et al, 1998;Segura et al, 2015) and might affect the incidence of human illnesses such as obesity, diabetes or hypertension (Ponnampalam et al, 2011;Gouk et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the C16:0 present in lard is located in the internal (Sn-2) position whereas, in palm oil it locates in the external (Sn-1 and Sn-3) positions (Small, 1991;Innis, 2011). This difference might be relevant in further processing for the industry of dry-cured products because FA distribution within the TAG molecule modifies the physical properties of the adipose tissue (Smith et al, 1998;Segura et al, 2015) and might affect the incidence of human illnesses such as obesity, diabetes or hypertension (Ponnampalam et al, 2011;Gouk et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In their review of the dietary effects of saturated fats, German and Dillard (2004) also state stearic acid is not thought to increase cholesterol concentrations and also discuss the importance of the TAG positions of the stearic acid groups on the molecule. Further evidence, from studies on mice metabolism, in support of both positional effects and of the role of stearic over palmitic acid in reducing fat deposition is offered by Gouk et al (2013Gouk et al ( , 2014. In the presence of calcium it is then poorly absorbed.…”
Section: Dietary Impact Of Stearic Acidmentioning
confidence: 99%
“…Hence, fatty acid distribution cannot be predicted before CIE, thus the application of end products from CIE will be hardly categorized as specific type of oils. Gouk and co-workers found that long chain fatty acids at sn-1,3 positions exhibited more profound effect in reducing body fat deposition in mice rather than total fatty acid compositions sn-1,2,3 8,9 because the snposition in the TG molecule determines the physical characteristic of fats, affects the absorption of fatty acids, lipid metabolism and fat distribution in tissues 10 . Previous studies indicated that unsaturated fatty acids at 2-position of triglycerides play an important role in regulating cholesterol levels in the bloodstream 11,12 .…”
Section: Introductionmentioning
confidence: 99%